Supporting Resilient Coastal Economies in Vietnam : Informing the operationalization of Vietnam’s Marine Strategy with international experiences - World Bank (Washington, DC : World Bank, 2022)
Inclusive and environmentally sound sustainable development re - quires managing natural resources that societies depend on for the long term. In the context of marine and coastal resources which pro - vide an important source of income for large numbers of households and revenue for countries, this implies balancing the economic, social, and environmental dimensions of the use of the natural resources in marine and coastal areas. The term “blue economy” is increasingly being used to describe this balanced approach. For coastal countries such as Vietnam, the importance of its marine economy is well known. The country has used the goods and services provided by the natural assets in its near-shore and coastal areas - including fisheries, mangroves, wetlands, lagoons, and sandy beaches - for tourism, production of seafood, and controlling climate events that cause erosion and weathering. The purpose of this report is to inform the operationalization of the strategy for the sustainable development of Vietnam’s marine economy by 2030, with a vision to 2045 by providing relevant insights from international experiences with blue economy development. The World Bank definition for blue economy - to promote economic growth, social inclusion, and preservation or improvement of livelihoods while at the same time ensuring environmental sustainability – is used as a guiding framework for this work.